ANALISIS FAKTOR â€“ FAKTOR YANG MEMPERNGARUHI MINAT BERTRANSAKSI MENGGUNAKAN E-COMMERCE - Putri Nasucha; Syaiful Syaiful (PROCEEDING UMSURABAYA, 2022)
As a growing transaction dealer, E-commerce has many risks and uncertainties compared to conventional transactions, but e-commerce users continue to increase. For this reason, the purpose of this study is to find out what is behind a person's interest in transacting using e-commerce. This research method uses quantitative methods with multiple linear regression analysis techniques. The sample of this research is accounting student of Muhammadiyah University of Gresik. The results showed that the variables of convenience, subjective norms, and knowledge of AIS had an effect on the interest in transacting using e-commerce, while the security variables and risk perception had no effect on the interest in transacting using e-commerce. From the results of this study, recommendations for further research are expected to be able to add new variables, not only using the questionnaire method and can expand the population.Keywords: Convenience; Interests in Transactions Using E-Commerce; Knowledge of SIA; Perceptions of Risk;Â  Security; Subjective Norms